STANDAR OPERASIONAL PROSEDUR PENJAMINAN MUTU DI LEMBAGA PENDIDIKAN ISLAM - Muhammad Taufiqurahman; Siti Julaiha; Bahrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of Standard Operating Procedures (SOPs) is a strategic instrument for strengthening the Internal Quality Assurance System (SPMI) in Islamic educational institutions. This study aims to examine the urgency of SOPs, the mechanism for their development, and the main obstacles to their implementation in quality assurance practices. The study used library research with a qualitative descriptive analytical approach. Data were collected through documentation of books, regulations, and relevant scientific literature, then analyzed using content analysis through data reduction, data presentation, and conclusion drawing. The findings show that SOPs help translate institutional quality policies into measurable, consistent, and accountable operational procedures. SOPs also support the quality assurance cycle through standard setting, implementation, evaluation, control, and continuous improvement. The main obstacles include organizational resistance, limited managerial literacy, limited digital infrastructure, and weak coordination among institutional units. These obstacles can be addressed through participatory SOP development, transformational leadership, staff training, digitalization of SOP documents, periodic internal quality audits, and a reward system for compliant work units. Therefore, SOPs should not be treated only as administrative documents, but as practical instruments for building sustainable quality culture in Islamic educational institutions.